A multi-epitope vaccine incorporating adhesin-derived antigens protects against Mycobacterium tuberculosis infection and dissemination - Yang, Haoyan; Lei, Xinkui; Chai, Siyu; Zhang, Sigen; Su, Guimin; Du, Lin (Frontiers in Immunology, 2025)
IntroductionAdhesion to host cells is the first and essential step in Mycobacterium tuberculosis (M. tuberculosis) infection. Among adhesion molecules, the PGRS domain of PE_PGRS33 plays a critical role in invasion but is dominated by B cell epitopes and lacks sufficient T cell epitopes, restricting its capacity to induce a balanced immune response.MethodsTo overcome this limitation, we employed an integrative reverse vaccinology pipeline combining computational prediction and experimental validation. Helper and cytotoxic T lymphocyte epitopes were incorporated from multiple M. tuberculosis adhesins as well as other virulence-associated proteins, and adjuvant sequences were systematically evaluated in silico.ResultsAmong three multi-epitope constructs, the Toll-like receptor 2 (TLR2)-agonist and pan HLA DR-binding epitope (PADRE)-adjuvanted vaccine (TLR2-vaccine) emerged as the most promising candidate. In murine models, TLR2-vaccine induced strong antigen-specific antibody and IFN-γ responses, significantly reduced bacterial loads following H37Ra challenge, and effectively prevented extrapulmonary dissemination.DiscussionThese findings highlight the potential of adhesin-inclusive multi-epitope vaccines to elicit both humoral and cellular immunity and demonstrate how computational vaccinology can accelerate the development of targeted interventions against tuberculosis.